Linking empathy to visuospatial perspective-taking in gambling addiction. (April 2017) - Tomei, Alexander; Besson, Jacques; Grivel, Jeremy
Abstract: It has been demonstrated that people suffering from substance-related addictions are less empathic than their non-addicted counterparts. Our first aim was to verify if this is also true for behavioral addictions. We hypothesized that problem gamblers are less empathic than healthy controls. Our second aim was to identify a cognitive marker of empathy that could be targeted in cognitive rehabilitation strategies. We propose that a potential cognitive marker of empathy could be visuospatial perspective-taking. Specifically, we hypothesized that visuospatial perspective-taking performances are lower in problem gamblers compared to healthy controls and that these visuospatial performances predict empathy. Thirty-one non-gamblers, 24 healthy gamblers, and 21 problem gamblers performed a visuospatial perspective-taking task before completing the Interpersonal Reactivity Index (IRI; Davis, 1980; Davis, 1983). Problem gamblers had decreased empathy and lower performance at the visuospatial perspective-taking task than non-gamblers and healthy gamblers. Furthermore, we confirmed that visuospatial perspective-taking abilities predict empathy on the IRI dimensions of interpersonal perspective-taking and personal distress. The present study provides new evidence that reduced empathy is not limited to subjects with substance-related addictions; rather, it extends to behavioral addictions. Visuospatial perspective-taking may be a viable cognitive marker for use as a rehabilitation target of empathy. Highlights: Empathy has been observed to be reduced in substance-related addictions. Empathy is also reduced in gambling addiction. Two empathy dimensions are predicted by visuospatial abilities. Visuospatial abilities may be considered for empathy rehabilitation.